2009
DOI: 10.1590/s0102-311x2009000400022
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do Programa de Controle da Doença de Chagas em relação à presença de Panstrongylus megistus na região centro-oeste do Estado de Minas Gerais, Brasil

Abstract: The Brazilian National Chagas Disease Control Program (PCDCh)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 30 publications
2
25
0
7
Order By: Relevance
“…The area under study will continue to be monitored in the coming years as a maintenance strategy of municipal and community interest to determine the importance of preventing triatomines and CD in these places. As observed in other studies, after evaluation of surveillance activities, the population and local professional interest tends to rise, as reflected by a greater number of triatomine notifications in the years following the research (26) (27) .…”
Section: Discussionsupporting
confidence: 65%
“…The area under study will continue to be monitored in the coming years as a maintenance strategy of municipal and community interest to determine the importance of preventing triatomines and CD in these places. As observed in other studies, after evaluation of surveillance activities, the population and local professional interest tends to rise, as reflected by a greater number of triatomine notifications in the years following the research (26) (27) .…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, notifications from PITs are, in general, intradomiciliaries 35 . Peridomiciliary captures occurred mainly after the research of public health agents in households, as observed by Villela et al 17 . Because secondary data were used, a lot of information, such as sampling location, species, and location (address), was lost due to incorrect completion of forms.…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 87%
“…In spite of the low indices for natural infection with trypanosomes for this species in DF, compared with studies in different regions of Brazil [12][13][14][15][16][17] , it is important to stress that some of the triatomines were found colonizing intradomicile and feeding on human blood according to precipitin tests (unpublished data), thus evidencing the risk of human infection. Our results also show that the spatial occurrence of triatomine species is different in the 20 administrative regions studied in DF, with the highest number of records and species richness observed in Planaltina, a predominantly rural region with the highest frequency of T. sordida.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations